Escarabeíneos (Coleoptera : Scarabaeidae : Scarabaeinae) associados aos excrementos de elefantes (Elephas maximus) introduzidos em uma savana neotropical - Sehn, Heivanice (2021)
The introduction of asian elephants Elephas maximus Linnaeus, 1758 in a neotropical savanna (Sanctuary of Elefantes Brasil) allowed to verify which species of native dung beetles frequent the excrements of these animals, and as to their association with other types of available excrements. In addition to elephant droppings, fresh horse droppings (Equus ferus Boddaert, 1785), tapirs (Tapirus terrestris Linnaeus, 1758), cattle (Bos taurus Linnaeus, 1758) and human (Homo sapiens sapiens Linnaeus, 1758) were used. Trap collections and direct excrements search resulted in a total of 2,261 specimens, representing 39 species and 13 genera. Four species not found in the traps were collected by direct collection from elephant droppings. The following species seem to show preference for elephant droppings over the others: Ateuchus latus (Boucomont, 1928), Ateuchus viduus (Blanchard, 1846), Dichotomius bos (Blanchard, 1846), Dichotomius cuprinus (Felsche, 1901) and Dichotomius opacus (Blanchard, 1846). The new resource attracted generalist consumers of all sizes, mostly paracoprid dung beetle species.